Analisis Wacana Naskah Pidato Internasional Susilo Bambang Yudhoyono: Tinjauan Linguistik Kritis - Anggara Jatu dan F.X. Kusumawati dan Nadar (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
President Susilo Bambang Yudhoyono (SBY) image building can be represented through many ways, one of them reflected on his international speeches. On this way, argumentation phases in the speeches can form social construct, self image, public opinion, new meaning and world-view. Based on critical linguistic point of view, word choice, sentence arrangement, and sentence pattern on speeches show a language expertise. This research aims at describing grammar used of SBY international speeches related with self image building.This research uses critical linguistics approach proposed by Fowler (1979) via Young and Harrison (2004:3) which focuses on two metafunctions of Systemic Functional Linguistics Halliday, ideational and textual function. The source of data are mine texts of SBY’s international speech in the tear of 2011 chosen based on some criteria; updated topics, variation of topics, and abundant data. Then, data are chosen, noted, and identified based on formulation of the problems. On data analysis, Norman Fairlough framework applied in analyzing the data. Based on limitation of Halliday’s metafunction, only were two levels chosen; textual analysis and social practice analysis. Besides, relevant studies were done to get detail and complete explanation.Based on data analysis, the result that can be emphasized is the grammar seen from word choice, clause, and sentence element, figures of speech, pattern of clause change are means to convey new meaning based on who is the speaker and psychological effect shown to listeners. Thus, it can reveal the speaker purpose extensively and help to describe argumentative phase on speeches. Those three results of research are efforts to build SBY self image on language expertise. On this way, SBY can attract sympathy, therefore international cooperation can run smoothly.